Hospitalization due to Adverse Drug Reactions and Drug Interactions before and after HAART - Michelle M Foisy; Kevin Gough; Corinna M Quan; Kevin Harris; Dominique Ibanez; Anne Phillips (Canadian Journal of Infectious Diseases)
OBJECTIVE: To characterize and compare the rates of adverse drug reactions (ADRs) and interactions on admission in two, one-year periods: pre-highly active antiretroviral therapy (HAART) (phase 1) and post-HAART (phase 2).